Independent Electrical Energy Environmental Friendly - TRI WATININGSIH; - KHOLISTIANINGSIH; PINGIT BROTO ATMADI (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2013)
SUMMARYElectrical energy in Indonesia is getting reduced because of Indonesia's population isincreasing with the increasing population, increasing electrical energy user and plant lisreikbeen sought but for remote areas still not reached by the flow of electricity . So that remoteareas have not been able to enjoy electrical energy trying to harness the flow of the riverclosest to making water mill , micro-hydro power , wind power , and solar power are nowbeing developed with the development of technology many new discoveries about alternativeelectrical energy that can be developed . Provision of electric power issues become obstaclesfor the government because the cost is not small the presence of alternative energy can helpthe government to solve the existing problems Is in line with the need to increase communityparticipation to meet electricity needs in remote areas through the development of alternativeenergy technologies as an Independent Power Plant is primarily to the utilization ofenvironmentally friendly fish pond that is our environment by making power plants pond /aquarium .Keywords : pool , Windmill . Batteries , generators , electrical energy .